Systematic Review: Strategi Humas Perguruan Tinggi dalam Meningkatkan Citra dan Reputasi melalui Media Sosial - Ubaidillah, Aan Fardani; Rochmah, Luthfi Maulida; Sobri, Ahmad Yusuf (Proceedings Series of Educational Studies, 2024)
AbstractThis research is a systematic review which aims to analyze Public Relations (PR) strategies in higher education in improving their image and reputation through social media. In this article, researchers conducted an in-depth review of various previous research articles indexed nationally and internationally to identify strategies used by higher education public relations. The results of this research reveal a comprehensive picture of effective strategies in building a positive image and reputation through social media. Some strategies that are often implemented involve creative content management, active interaction with the audience, conceptualized branding campaigns and the use of different social media platforms according to specific communication goals. Active involvement on social media has also been proven to play an important role in forming positive perceptions of higher education. The conclusions of this research can provide guidance for higher education public relations practitioners in developing and implementing effective communication strategies via social media with the aim of improving the image and reputation of educational institutions. This research provides valuable insights for the development of PR practitioners in the context of higher education in the digital era.Keywords: Higher Education Public Relation; Image and Reputation; Social Media AbstrakPenelitian ini merupakan suatu tinjauan sistematis yang bertujuan untuk menganalisis strategi Hubungan Masyarakat (Humas) di perguruan tinggi dalam meningkatkan citra dan reputasinya melalui media sosial. Dalam artikel ini, peneliti melakukan tinjauan mendalam terhadap berbagai artikel penelitian terdahulu yang terindeks secara nasional maupun internasional untuk mengindentifikasi strategi yang digunakan oleh Humas perguruan tinggi. Hasil penelitian ini mengutarakan gambaran yang komprehensif tentang strategi yang efektif dalam membangun citra dan reputasi positif melalui media sosial. Beberapa strategi yang sering diimplementasikan melibatkan pengelolaan konten kreatif, interaksi aktif dengan audiens, kampanye branding yang terkonsep dan pemanfaatan platform media sosial yang berbeda sesuai dengan tujuan komunikasi tertentu. Keterlibatan aktif di media sosial juga terbukti berperan penting dalam membentuk persepsi positif terhadap perguruan tinggi. Kesimpulan dari penelitian ini dapat memberikan panduan bagi praktisi Humas perguruan tinggi dalam menyusun dan mengimplementasikan strategi komunikasi yang efektif melalui media sosial dengan tujuan meningkatkan citra dan reputasi institusi pendidikan. Penelitian ini memberikan wawasan yang berharga bagi pengembangan praktisi Humas dalam konteks perguruan tinggi di era digital.Kata kunci: Humas Perguruan Tinggi; Citra dan Reputasi; Media Sosial